Design, synthesis and evaluation of benzoheterocycle analogues as potent antifungal agents targeting CYP51. Issue 12 (23rd July 2018) - Zhao, Shizhen; Wei, Peng; Wu, Mengya; Zhang, Xiangqian; Zhao, Liyu; Jiang, Xiaolin; Hao, Chenzhou; Su, Xin; Zhao, Dongmei; Cheng, Maosheng
Graphical abstract: Highlights: 26 new compounds with benzoheterocycle scaffolds were designed and synthesized. The naphthoisoxazole was selected to improve activity against Aspergillus spp. Compounds 13s and 14a showed better antifungal activity than fluconazole. Compound 13s reduced the content of ergosterol in a dose-dependent manner. Compounds 13s and 14a exhibited low inhibition profiles for human cytochrome P450 isoforms. Abstract: To further enhance the anti- Aspergillus efficacy of our previously discovered antifungal lead compound 1, a series of benzoheterocycle analogues were designed, synthesized and evaluated for their in vitro antifungal activity. The most promising compounds 13s and 14a exhibited excellent antifungal activity against C. albicans, C. neoformans, A. fumigatus and fluconazole-resistant C. albicans strains, that was superior or comparable to those of the reference drugs fluconazole and voriconazole. GC–MS analyses suggested that the novel compound 13s might have a similar mechanism to fluconazole by inhibiting fungal lanosterol 14α-demethylase (CYP51). Furthermore, compounds 13s and 14a exhibited low inhibition profiles for various human cytochrome P450 isoforms as well as excellent blood plasma stability.